The Role of Toll-Like Receptor 4 in Infectious and Noninfectious Inflammation - Monica Molteni; Sabrina Gemma; Carlo Rossetti (Mediators of Inflammation)
Toll-like receptor 4 (TLR4) belongs to the family of pattern recognition receptors (PRRs). They are highly conserved receptors that recognize conserved pathogen-associated molecular patterns (PAMPs), thus representing the first line of defense against infections. TLR4 has been long recognized as the sensing receptor for gram-negative lipopolysaccharide (LPS). In addition, it also binds endogenous molecules produced as a result of tissue injury. Hence, TLR4 represents a key receptor on which both infectious and noninfectious stimuli converge to induce a proinflammatory response. TLR4-mediated inflammation, triggered by exogenous or endogenous ligands, is also involved in several acute and chronic diseases, having a pivotal role as amplifier of the inflammatory response. This review focuses on the research progress about the role of TLR4 activation in infectious and noninfectious (e.g., sterile) inflammation and the effects of TLR4 signaling in some pathological conditions.